Cursos Extracurriculares (Inglés) y el rendimiento académico de estudiantes de segundo de secundaria. I.E. Santa Edelmira, Trujillo 2018 - Sernaque Arevalo, Wendy Melissa (2019)
This research entitled: Extracurricular Courses (English) and Academic Performance of second grade secondary students Santa Edelmira school, Trujillo 2018, had as its main objective to determine the influence of English extracurricular courses on the academic performance of the English language of the second grade secondary students of the Santa Edelmira school Also, an extracurricular English course was designed and applied to second grade secondary students of the Santa Edelmira school. At the same time, it sought to identify the academic level of the English language in the Oral Comprehension and Production, Text Comprehension and Text Production dimensions of the second grade secondary students of the Santa Edelmira school; before and after the application of the extracurricular English course. To achieve these objectives, two instruments for data collection were applied; an observation guide and a Test; considering the contents of the cycle they were studying and the expected level for second-year secondary school students. The population consisted of 89 second-year secondary students of the Santa Edelmira school, in 2018 and the sample, by 36 students, which formed a mixed group, and had as a common characteristic, the low academic performance in the English course; The sample was taken for convenience. The data was meticulously analyzed and the result obtained was that English extracurricular courses do have a significant influence on academic performance of the English language